Do Ricorse Potentially Able to Diminish Student’s Cognitive Learning Outcomes on Different Academic? - Nurul Ika Noviyanti; Susriyati Mahanal; Siti Zubaidah (Jurnal Pendidikan Sains, 2018)
Abstract: Learning outcomes are the students’ ability after receiving learning experience. In fact, there are gap in students’ cognitive learning outcomes. This gap can be minimized by learning model. The purpose of this research was to investigate the RICOSRE learning model potency in learning outcomes gap on different academic ability. The current study was design as a quasi-experiment with pre-test post-test non-equivalent control group design. Based on data analysis, RICOSRE learning model is able to improve cognitive learning outcomes, so, the students’ learning outcomes gap in school with different academic ability is getting closer.Key Words: cognitive learning outcome, RICOSRE learning model, academic abilityAbstrak: Hasil belajar adalah kemampuan siswa setelah menerima pengalaman belajar. Faktanya masih terjadi kesenjangan hasil belajar kognitif siswa. Kesenjangan ini dapat diperkecil dengan model pembelajaran. Tujuan penelitian ini untuk mengetahui potensi model pembelajaran RICOSRE dalam mempersempit kesenjangan hasil belajar kognitif pada siswa dengan kemampuan akademik berbeda. Desain penelitian menggunakan kuasi ekperimen dengan pre-test-post-test non equivalen control group design. Berdasarkan analisis data, model pembelajaran RICOSRE mampu meningkatkan hasil belajar kognitif siswa dengan kemampuan akademik rendah dan tinggi, sehingga kesenjangan hasil belajar kognitif siswa pada sekolah dengan kemampuan akademik berbeda semakin kecil.Kata kunci: hasil belajar kognitif, model pembelajaran RICOSRE, kemampuan akademik